Pengaruh Motivasi Kerja, Kompetensi, Dan Kompensasi Terhadap Kinerja Pegawai Pada Kantor Pelayanan Pajak Pratama Makassar Selatan - Muhammad Dirham Azis (Jurnal Aplikasi Manajemen, Ekonomi dan Bisnis, 2018)
The purpose of this study was to: 1) analyze the effect of competence, motivation, and promotion on the performance of employees at Tax Primary Office South Makassar, and 2) determine the dominant variables affect the performance of employees at Tax Primary Office South Makassar. The data used are primary data and secondary data. The study population were all employees of the Tax Primary Office South Makassar totaling 81 people, due to a limited population, the entire population is used as a respondent. Data collected through questionnaires, and documentation. The method of data analysis using descriptive statistical analysis, and multiple linear regression using SPSS program. The results showed that the competence, motivation, and promotion have significant and positive impact on the performance of employees at Tax Primary Office South Makassar. Of the three independent variables used in this study, was the dominant influence competence in improving performance of employees at Tax Primary Office South Makassar